2021
DOI: 10.3390/electronics10141656
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach for a Unified Architecture for Type IV DCT/DST with an Efficient Incorporation of Obfuscation Technique

Abstract: This paper aims at solving one challenging problem in designing VLSI chips, namely, the security of the hardware, by presenting a new design approach that incorporates the obfuscation technique in the VLSI implementation of some important DSP algorithms. The proposed method introduces a new approach in obtaining a unified VLSI architecture for computing type IV discrete cosine transform (DCT-IV) and type IV discrete sine transform (DST-IV), with an efficient integration of the obfuscation technique, while main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Due to the unique characteristics of the utilized computational structure, it becomes feasible to efficiently integrate the obfuscation hardware security technique using methods similar to the ones described in [30].…”
Section: An Improvement Of the Proposed Algorithm For The Computation...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unique characteristics of the utilized computational structure, it becomes feasible to efficiently integrate the obfuscation hardware security technique using methods similar to the ones described in [30].…”
Section: An Improvement Of the Proposed Algorithm For The Computation...mentioning
confidence: 99%
“…These architectures have several merits over others, especially due to their regular and local data flow with an efficient input/output and data transfer operations, as in case of systolic arrays architectures. Thus, we have obtained efficient VLSI implementations of certain digital signal processing (DSP) algorithms that are using cyclic convolutions or circular correlations [23][24][25][26][27] that have been extended to some other regular and modular computational structures, such as, for example, skew-circular and pseudo-circular correlations or band-correlations [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In [28], is the authors presented a unified VLSI architecture for type IV DCT/DST that is the best reported in the literature, whereas we have eight computational structures implemented using eight short systolic arrays and where 2(N − 1) general multipliers and 2(N − 1) adders have been used. Because it uses general multipliers with a higher hardware complexity as compared to multipliers with a constant, it has a significantly higher hardware complexity.…”
Section: Related Workmentioning
confidence: 99%
“…The architectures described in [26,28,29] have been developed to facilitate the incorporation of hardware security techniques.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation